Double Crisis: Sport Mega Events and the Future of Public Service Broadcasting. (April 2021) - Lünich, Marco; Starke, Christopher; Marcinkowski, Frank; Dosenovic, Pero
Covering sport mega events is a pivotal strategy for public service broadcasting (PSB) to claim audience support and public legitimacy. However, these mega events are subject to considerable controversy due to their association with doping or corruption. This raises the question for the PSB of how to satisfy the audience of the Olympic Games: by looking closely or by looking away? Conducting two empirical studies, this article investigates how German public service broadcasters reported the sociopolitical problems related to the 2016 Olympic Summer Games and whether the coverage has met the expectations of the audience. The results of a content analysis suggest that a substantial amount of coverage was dedicated to the problematic aspects of the Games. A conjoint analysis shows that German public service broadcasters did not meet the expectations of different audience segments: Neither the core audience nor event-driven spectators and certainly not the outsiders of media sports were fully satisfied by the Olympic program menu of German PSB.